Microbiomes in a manganese oxide producing ecosystem in the Ytterby mine, Sweden: impact on metal mobility - Sjöberg, Susanne (FEMS Microbiol Ecol, 2020)
Microbe-mediated precipitation of Mn-oxides enriched in rare earth elements (REE) and other trace elements was discovered in tunnels leading to the main shaft of the Ytterby mine, Sweden. Defining the spatial distribution of microorganisms and elements in this ecosystem provide a better understanding of specific niches and parameters driving the emergence of these communities and associated mineral precipitates. Along with elemental analyses, high-throughput sequencing of the following four subsystems were conducted: (i) water seeping from a rock fracture into the tunnel, (ii) Mn-oxides and associated biofilm; referred to as the Ytterby Black Substance (YBS) biofilm (iii) biofilm forming bubbles on the Mn-oxides; referred to as the bubble biofilm and (iv) fracture water that has passed through the biofilms. Each subsystem hosts a specific collection of microorganisms. Differentially abundant bacteria in the YBS biofilm were identified within the Rhizobiales (e.g. Pedomicrobium), PLTA13 Gammaproteobacteria, Pirellulaceae, Hyphomonadaceae, Blastocatellia and Nitrospira. These taxa, likely driving the Mn-oxide production, were not detected in the fracture water. This biofilm binds Mn, REE and other trace elements in an efficient, dynamic process, as indicated by substantial depletion of these metals from the fracture water as it passes through the Mn deposit zone. Microbe-mediated oxidation of Mn(II) and formation of Mn(III/IV)-oxides can thus have considerable local environmental impact by removing metals from aquatic environments.